Any Port in a Storm; how the sounds of the ocean played through sound conditioners offer more than just a sleep aid. (4th May 2022) - Harris, Amy
ABSTRACT: Relationships with the ocean have a complex legacy that impacts much of our modern lives. John Durham Peters argues that the ocean contributes much toward our understanding of ourselves, even calling it the "medium of all media" because it is from there that we once emerged. In considering one particular form of technology that draws from the ocean for its success, this paper considers the role of sound conditioners and their use of ocean sounds to combat insomnia. From a soundwalk along the ocean front conducted in person, to examining the impetus for the original sound conditioner and recordings of the ocean, a brief media history is undertaken to give context. The main body of the paper covers three areas: by drawing on affect theory we understand the emotional impacts of the technology; by engaging with colonial history the inherent legacy of extractivism is revealed; and finally by looking at these mediations through Indigenous perspectives, we can see the embedded history clearly and find ways to productively move forward. This paper aims to understand what it means to listen to a recorded, manipulated, edited sleep soundtrack, and why we have need for such a tool.